SCREENING FOR ANOMALIES IN OCCIPITO-CERVICAL JUNCTION USING CRANIOMETRY IN COMPUTED TOMOGRAPHY - MR. MADHAVAN T.S; MS. WINNIECIA DKHAR (International Journal of Pharma and Bio Sciences, 2016)
The aim of this study is screening for anomalies in Occipito-Cervical Junction using craniometry in Computed Tomography. In this study 170 patients undergo CT of cervical spine on MDCT Brilliance 64 slice Phillips with normal routine protocol and later post processed into Multiplanar imaging where Craniometry was performed in the mid sagittal plane and Wackenheim-clivus baseline, clivus-canal angle , McRae line , Chamberlain line , McGregor line were calculated using the measurement tools. The present study brings in the significant role of Chamberlain’s line and McGregor’s line the as the deviation of the measured values from standard values which confirms the abnormality within the anatomical structure and hence helpful for the physicians especially for the ortho-surgeons to diagnose and provide appropriate management either clinically or surgically in the early stage.